🎓 (s-2t)(t-3s)+(2s-t)(3t-s) - Odrabiamy.pl

Matematyka
 -  gimnazjum

Matematyka
 -  gimnazjum

(s-2t)(t-3s)+(2s-t)(3t-s)

Aga
89146
odpowiedziała na to pytanie
(s-2t)(t-3s)+(2s-t)(3t-s)=s٠t+s٠(-3s)+(-2t)٠t+(-2t)٠(-3s)+2s٠3t+2s٠(-s)+(-t)٠3t+(-t)٠(-s)=st-3s²-2t²+6st+6st-2s²-3t²+st=-5s²+14st-5t²
Wideolekcja
content
1 kwietnia 2019
Chemia

Nazwij sole: MgCO3, KCl , FeS

około 8 godzin temu
Wideolekcja
content
2 kwietnia 2019
Matematyka

(2x-1)² ≥ 3x - 2

około 10 godzin temu
Wideolekcja
content
25 marca 2019
Matematyka
(s-2t)(t-3s)+(2s-t)(3t-s)
15 października 2018